The relationship between screen time exposure and the presence of anxiety-related disorders among adolescents during the COVID-19 pandemic: A cross-sectional study - Rasha Rashad Alsaigh; Ghadeer Essam Assas; Nashwa Hussain Yahia; Najwan Faisal Sharaf; Shahad Fareed Shaikh; Hadeel Majed Alghamdi; Hanan Abdullah Badr; Salmah Awad Alghamdi (Belitung Nursing Journal, 2022)
Background: The Coronavirus Disease 2019 (COVID-19) pandemic prompted rules and laws such as lockdown, which contributed to staying at home and participating in sedentary activities such as using smartphones, tablets, televisions, gaming devices, and computers. As a result of the increased use of digital screen time, a worldwide issue has arisen among various age groups, especially adolescents, which may have affected their psychological well-being, increasing their susceptibility to anxiety-related disorders. Objective: This study aimed to assess the relationship between screen time exposure and the presence of anxiety-related disorders among adolescents during the COVID-19 pandemic. Methods: A quantitative descriptive cross-sectional design using convenience sampling was used in this study. The online self-administered questionnaire, including the Arabic-translated version of the Screen for Child Anxiety-related Disorders (SCARED-C), was distributed through social media using Google forms between February and April 2021. The Chi-Squared test was used for data analysis. Results: Of 625 participants, majority were females (n = 527, 84.3%) than males (n = 98, 15.7%). A significant difference between screen time and the presence of an anxiety-related disorder among adolescents during the COVID-19 pandemic (p = .021) was noted. More than half of the participants (n = 410, 65.6%) scored above 25 in the SCARED-C test, indicating the presence of an anxiety-related disorder regardless of the type. Of those, more than a quarter (n = 176, 28.2%) used screens for more than 8 hours a day. Conclusion: The results indicated a relationship between screen time exposure and the presence of anxiety-related disorders among adolescents during the pandemic. In particular, adolescents are more susceptible to the adverse effects of increased exposure to screen time, which is constantly on the rise. Therefore, nurses and other healthcare professionals can play a significant role in providing guidance and advice to parents, caregivers, and adolescents themselves on how to limit screen time exposure. The findings can also be useful for future studies to build on and develop screen time management interventions and guidelines.